Monitoring & evaluation of mangroves in Guyana (Storymap) - Castaño, Silvia-Elena; Feldman, Nurymar; Herndon, Kelsey; Zutta, Brian; Chan-Bagot, Kim (2022)
Establish a monitoring & reporting system for tracking extent & structure of coastal mangroves in Guyana. Mangroves retain carbon dioxide (CO₂) emissions. They can store up to 10 times more carbon than land-based forests and are estimated to capture and store 34 million tons of carbon globally. Mangroves protect the lives of inhabitants of coastal areas from floods, hurricanes, and tsunamis. Figures indicate that a mangrove forest of 500 meters reduces the wave height by 50 to 90%. https://storymaps.arcgis.com/stories/66927fb7a9994f8ca8fd9365d0beefef